2013
DOI: 10.1097/wnr.0b013e3283627993
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous activity in antisocial personality disorder revealed by regional homogeneity

Abstract: There is increasing evidence that antisocial personality disorder (ASPD) stems from brain abnormalities. However, there are only a few studies investigating brain structure in ASPD. The aim of this study was to find regional coherence abnormalities in resting-state functional MRI of ASPD. Thirty-two ASPD individuals and 34 controls underwent a resting-state functional MRI scan. The regional homogeneity (ReHo) approach was used to examine whether ASPD was related to alterations in resting-state neural activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Tang et al (131) investigated resting-state neural activity in ASPD and found that ASPD subjects showed decreased activity in the posterior cerebellum and middle frontal gyrus (MFG). Contrariwise, ASPD subjects showed increased activity in the middle occipital gyrus, inferior temporal gyrus, and inferior occipital gyrus (130). Similarly, Liu, Liao, Jiang, and Wang (132) found decreased activity in the posterior cerebellum, but also in temporal areas and in the orbitofrontal cortex.…”
Section: Functional Mri Findings In Aspdmentioning
confidence: 82%
See 2 more Smart Citations
“…Tang et al (131) investigated resting-state neural activity in ASPD and found that ASPD subjects showed decreased activity in the posterior cerebellum and middle frontal gyrus (MFG). Contrariwise, ASPD subjects showed increased activity in the middle occipital gyrus, inferior temporal gyrus, and inferior occipital gyrus (130). Similarly, Liu, Liao, Jiang, and Wang (132) found decreased activity in the posterior cerebellum, but also in temporal areas and in the orbitofrontal cortex.…”
Section: Functional Mri Findings In Aspdmentioning
confidence: 82%
“…These heritable disorders reflect independent structural and functional aberrancies in the brain, but also seem to manifest convergent biological processes to some extent. For example, both CD and ASPD are related to dysfunction of the default mode network (93,130) and to decreased GMV in limbic and cortical regions (31,128). Further, the said disorders are not mutually exclusive nor are they biologically dichotomic constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence indicates that these abnormalities are related to deficits in the prefrontal cortex, temporal cortex, insula, angular gyrus, parahippocampus, and anterior/posterior cingulate gyrus. In our previous studies, we investigated ASPD-related changes in the regional homogeneity (ReHo) by using resting-state functional MRI (R-fMRI) data, and we found that the ASPD individuals show reduced ReHo in the middle frontal gyrus and elevated ReHo in the inferior temporal gyrus 3 . In another functional connectivity study 4 , we determined that ASPD-associated changes occur primarily within and across the default-mode network (DMN).…”
mentioning
confidence: 99%
“…The MTG exhibited the highest discriminate power within the DMN to distinguish individuals with antisocial personality disorder from controls and the cerebellum enabled the best differentiation overall (Tang, Jiang, et al , 2013). For the MTG, other rs-fMRI studies reported increased functional activity in adults with antisocial personality disorder (Tang, Liu, et al , 2013) and CU-related decreased rsFC in prison inmates (Espinoza et al , 2018). Cerebellar and opercular regions have been implicated in CU-related rsFC alterations in adults (Philippi et al , 2015) and juveniles (Aghajani et al , 2016) and left insula in CU-related rsFC (Werhahn et al , 2018), emotions (Lindquist et al , 2012), and empathy (Lockwood et al , 2013).…”
Section: Discussionmentioning
confidence: 97%